Variational Sequences, Representation Sequences and Applications in Physics - Palese, M.; Rossi, O.; Winterroth, E.; Musilová, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
This paper is a review containing new original results on the finite order variational sequence and its different representations with emphasis on applications in the theory of variational symmetries and conservation laws in physics.